WAJAH BURAM PELAYANAN PUBLIK PASCA OTONOMI DAN PEMILUKADA - Sirajudin, Sirajudin (Jurnal Konstitusi, 2011)
Giving rooms to local government to local autonomy and direct election of local heads has not changed the face of public service to become better and more elegant. Reengineering is needed through consistent and continuous institutionalisation of standar service and reformation of the public service apparatus in order to make the public service take more side to the aspiration and interest of local societies.